2012
DOI: 10.3133/sir20125133
|View full text |Cite
|
Sign up to set email alerts
|

Topographic change detection at select archeological sites in Grand Canyon National Park, Arizona, 2007-2010

Abstract: This report and any updates to it are available online at: http://pubs.usgs.gov/sir/2012/5133/ For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprod To order this and other USGS information products, visit http://store.usgs.gov Any use of trade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Terrestrial laser scanning (TLS) is a useful technology for rapid, detailed measurement of erosion/deposition patterns [ Collins and Sitar , ; Wheaton et al , ; Day et al , ; Lague et al , ] and changes in surface roughness [ Sankey et al , ; Lague et al , ]. Because the data acquisition process is relatively efficient, noninvasive [ Collins et al , ], and suitable for steep terrain [ Staley et al , ]; repeat surveys over a period of weeks to years make it possible to detect centimeter‐scale changes in topography over time [ Wheaton et al , ; Schmidt et al , ; Soulard et al , ; Staley et al , ]. Studies in the steep shrublands of the San Gabriel mountains, California, have demonstrated the potential of TLS to quantify post‐fire morphologic change [ Schmidt et al , ; Staley et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Terrestrial laser scanning (TLS) is a useful technology for rapid, detailed measurement of erosion/deposition patterns [ Collins and Sitar , ; Wheaton et al , ; Day et al , ; Lague et al , ] and changes in surface roughness [ Sankey et al , ; Lague et al , ]. Because the data acquisition process is relatively efficient, noninvasive [ Collins et al , ], and suitable for steep terrain [ Staley et al , ]; repeat surveys over a period of weeks to years make it possible to detect centimeter‐scale changes in topography over time [ Wheaton et al , ; Schmidt et al , ; Soulard et al , ; Staley et al , ]. Studies in the steep shrublands of the San Gabriel mountains, California, have demonstrated the potential of TLS to quantify post‐fire morphologic change [ Schmidt et al , ; Staley et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The form and components of this equation are similar to the one used by Brasington et al [23] for propagating uncertainty to change detection work with DoD analysis; however, the equation of Collins et al [29] deals more explicitly with the sources of error involved in point cloud change detection. The uncertainty of the OPUS positions used in 2011 and 2012 are not considered in this error analysis, because inter-year comparisons of the feature are not undertaken in this study.…”
Section: Change Detection Methods I: C2mmentioning
confidence: 82%
“…Two error analysis techniques were used to calculate a change detection threshold to be used in conjunction with CbD to differentiate noise from measurable topographic change. Collins et al [29] proposed an additive RMS error analysis technique to estimate the accumulated errors associated with (1) the GPS solutions used for georeferencing; (2) the instrument; (3) the georeferencing itself; and (4) the registration of multiple point clouds. This error estimate can then be used to assess whether measured changes between two point clouds are significant.…”
Section: Change Detection Methods I: C2mmentioning
confidence: 99%
See 2 more Smart Citations